FRBR jako model danych bibliograficznych dla bibliotekarza i użytkownika końcowego - Paleczna, Dominika (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The aim of the article was to show advantages and disadvantages of FRBR, furthermore to consider if it is useful for end users. Functional Requirements for Bibliographic Records (FRBR) was described. Two ways of implementing FRBR in a library catalog were presented – in Virtua ILS and Primo discovery system. Bibliographic records’ presentation for end users in Virtua and Primo was analyzed. Necessity of implementing FRBR was recognized, especially for end users convenience.